Strengthening Hospital Infection Control Programs Through Coordinated Practices Across Pharmacy, Nursing, Sterilization, Operating Room, And Health Administration Units (The Review of Diabetic Studies, 2024)
Introduction: Hospital-acquired infections can seriously harm patient safety and lower the quality of healthcare. Effective prevention needs everyone working together, including pharmacists, nurses, people who sterilize equipment, staff in operating rooms, and those in health administration.Objective of Work: To check how well different teams working together can prevent hospital-acquired infections and make patients healthier. Methods: A review of existing literature was done, looking at research on teamwork across different fields, responsible use of antibiotics, patient care by nurses, rules for keeping things clean and safe, safety in surgery areas, and how management oversees these activities. Findings: Coordinated programs reduce infection rates. Pharmacy-led antimicrobial stewardship, nursing actions, correct sterilization practices, proper surgical procedures, and strong administrative support all help make healthcare safer and more efficient.Conclusion: When different medical teams work together, it helps prevent infections, reduces hospital-acquired infections, and improves how well patients recover. Hospitals that have combined programs show clear results in making care safer and better.